The Spiritual Anguish in John Webster’s The Duchess of Malfi - Neupane, Dipesh (Cognition, 2023)
This paper attempts to explore the fusion between the mundane world and the world of spirituality and religiosity in the paly- The Duchess of Malfi. It shows how two worlds are inseparable and how their integrity is inevitable in human life. Whatever mundane and material life people live, they ultimately seek the blessings from the supreme divine to attain the peace and bliss. Since death is the ultimate destination life, ultimately people idealize it as the gate to enter into the world of eternity. This study attempts to answer the questions: why and how do people of the mundane world surrender to the supreme divinity ultimately? and what circumstances lead people to utter the name of heavenly abode? This paper conceptualizes the theoretical frameworks of spiritualism to invigorate the study in the play. The contrast and the fusion between Materialism and Spiritualism are remarkable aspects of this study. The life of the duchess of Malfi and her tragic end with her spiritual anguish echo the value of the amalgamation between the spiritual life and the material visions. It is difficult for human beings to escape from spiritual outpourings at the time of sufferings, hardships and even the tragic end i.e. death. Therefore, human life becomes complete, meaningful and worth living only through the combination of both notions. Life lived in isolation form spiritual notions does not become saucy and juicy. The supremacy of the spiritual over the physical, of the soul over the body is asserted in this study to make people conscious of his spiritual superiority in life.